Suplementasi Mineral Lokal untuk Perbaikan Nutrisi dan Reproduksi Sapi Peranakan Simmental Dara pada Peternakan Rakyat di Jorong Sibaladuang, Kabupaten Limapuluh Kota - . Khalil; . Andri; Zaituni Udin (Institut Pertanian Bogor, 2019)
This community service was aimed to evaluate beneficial effect and constrains of mineral supplementation onfeed of Simmental heifers that be raised by smallholders. Mineral were formulated by using locally available materials (rock flour, limestone, fresh water oyster shell meal) and prepared in loose and lick-block forms. The local mineral formulas were fed to 24 Simmental heifers raised by 17 smallholders for 14 weeks in four treatments: P0 (no supplementation, control), P1 (supplemented with commercial mineral premix), P2 (supplemented with local mineral feed in loose meal), and P3 (supplemented with local mineral feed in form). Each treatment consisted of 6 heifers as replication. Parameters measured included: blood minerals (Ca, P, Mg) and blood hematology (hemoglobin (Hb), mean corpuscular Hb concentration (MCHC), total red blood cell (RBC), white blood cell (WBC), hematocrit concentration (HCT)), total protein, and estrus onset. Results showed that heifers supplemented with local minerals (P2 and P3) were detected earlier estrus onset than the control (P0) and that supplemented with commercial mineral premix (P1). Local mineral supplementation gave also positive effect on blood mineral, protein and hematological profiles, even though there were no statistically difference. It was concluded that mineral supplementation gave positive effect of reproduction performances and nutritional status of Simmental heifers. Local mineral offered in lick-block had better effect than that in loose form.